Mass Cultivation of Microalgae: I. Experiences with Vertical Column Airlift Photobioreactors, Diatoms and CO2 Sequestration - Hans Chr. Eilertsen; Gunilla K. Eriksen; John-Steinar Bergum; Jo Strømholt; Edel Elvevoll; Karl-Erik Eilertsen; Eldbjørg Sofie Heimstad; Ingeborg Hulda Giæver; Linn Israelsen; Jon Brage Svenning; Lars Dalheim; Renate Osvik; et al. (Applied Sciences, 2022)
From 2015 to 2021, we optimized mass cultivation of diatoms in our own developed vertical column airlift photobioreactors using natural and artificial light (LEDs). The project took place at the ferrosilicon producer Finnfjord AS in North Norway as a joint venture with UiT—The Arctic University of Norway. Small (0.1–6–14 m3) reactors were used for initial experiments and to produce inoculum cultures while upscaling experiments took place in a 300 m3 reactor. We here argue that species cultivated in reactors should be large since biovolume specific self-shadowing of light can be lower for large vs. small cells. The highest production, 1.28 cm3 L−1 biovolume (0.09–0.31 g DW day−1), was obtained with continuous culture at ca. 19% light utilization efficiency and 34% CO2 uptake. We cultivated 4–6 months without microbial contamination or biofouling, and this we argue was due to a natural antifouling (anti-biofilm) agent in the algae. In terms of protein quality all essential amino acids were present, and the composition and digestibility of the fatty acids were as required for feed ingredients. Lipid content was ca. 20% of ash-free DW with high EPA levels, and omega-3 and amino acid content increased when factory fume was added. The content of heavy metals in algae cultivated with fume was well within the accepted safety limits. Organic pollutants (e.g., dioxins and PCBs) were below the limits required by the European Union food safety regulations, and bioprospecting revealed several promising findings.